Therapeutic alliance with psychotherapist versus dietician: a pilot study of eating disorder treatment in a multidisciplinary team during the COVID-19 pandemic - Elran-Barak, Roni; Grundman-Shem Tov, Rinat; Zubery, Eynat; Lewis, Yael D. (Frontiers in Psychiatry, 2024)
Little is known about the therapeutic alliance (TA) formed with different professionals in multidisciplinary eating disorder (ED) treatment, particularly in the context of online treatment during the COVID-19 pandemic. We aimed to conduct a pilot study during the COVID-19 pandemic examining characteristics of patients' TA with their dieticians and psychotherapists, associations between patients' and therapists' views of the TA, and relationships between psychological characteristics and TAs. Sixty-three patients with EDs and their treating psychotherapists and dieticians were surveyed during the COVID-19 pandemic using the Working Alliance Inventory (WAI-S). Spearman correlation tests were used to examine associations between variables. Positive associations were found between the TAs examined.Concordance was stronger in patient-dietician dyads than in patient-psychotherapist dyads.Severe ED psychopathology was associated with weaker TA (bond subscale). General psychopathology was associated with weaker TA toward the dietician (task subscale). Given that several differences were found between the treatment dyads' TAs, further longitudinal studies are needed validate our pilot finings and to investigate multidisciplinary TAs and their impact on treatment outcomes in online ED treatment settings during the COVID-19 pandemic, as well as in other treatment settings (e.g., in-person settings). This will contribute to a deeper understanding of the dynamics of TAs in multidisciplinary ED treatment and inform the development of more effective interventions.